Ethnography of Communication in Empowering Women Farmers’ Group in Sodong Village - Eko Purwanto; Mirza Shahreza; Ade Rahmah; Umar Farisal (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2026)
This study aims to describe and analyze communication activities in the empowerment of the Women Farmers Group (KWT) in Sodong Village, Tangerang Regency. While previous studies on KWT often emphasize economic outcomes or program evaluations, there is a research gap concerning the strategic role of communication as a vehicle for social change embedded in local cultural contexts and gender relations. This research employs a qualitative approach with the ethnography of communication as the theoretical basis, utilizing Dell Hymes’ SPEAKING model to examine verbal and non-verbal interaction patterns. Data were collected through in-depth interviews, FGDs, and participant observation. The findings reveal that empowerment communication is structured through eight SPEAKING components, characterized by a familial atmosphere (key) in social spaces like Saung Kebun (setting), which fosters trust and openness. The participatory patterns effectively facilitate the diffusion of agricultural innovations and enhance social solidarity. This study contributes to the literature on community-based development by integrating communication, gender, and rural development perspectives, offering a strategic model for realizing sustainable Food Self-Sufficient Villages through inclusive collaboration.